2015
DOI: 10.1039/c5dt02805a
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of americium in seawater and accumulation in the marine sponge Aplysina cavernicola

Abstract: The fate of radionuclides in the environment is a cause of great concern for modern society, seen especially in 2011 after the Fukushima accident. Among the environmental compartments, seawater covers most of the earth's surface and may be directly or indirectly impacted. The interaction between radionuclides and the marine compartment is therefore essential for better understanding the transfer mechanisms from the hydrosphere to the biosphere. This information allows for the evaluation of the impact on humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…Previously, this method was successfully applied to the study of uranium, neptunium and americium in natural seawater. X‐ray Absorption Spectroscopy (XAS) was performed together with Time Resolved Laser Fluorescence Spectroscopy for uranium(VI) ,…”
Section: Figurementioning
confidence: 99%
“…Previously, this method was successfully applied to the study of uranium, neptunium and americium in natural seawater. X‐ray Absorption Spectroscopy (XAS) was performed together with Time Resolved Laser Fluorescence Spectroscopy for uranium(VI) ,…”
Section: Figurementioning
confidence: 99%
“…Reiller et al 15,16 performed inductive analysis of the existing migration law of Am and associated it with rare-earth elements; they concluded that when the pH of the solution is less than 7, between 7 and 8.5, and above 8.5, the main complex ions are RE 3+ , RECO 3 + and RE(CO 3 ) 2 À , and possibly RE(CO 3 ) 3 3À or higher-valence-state complex ions, respectively. Given similarities in the physicochemical properties of Am and rareearth elements, Maloubier et al 17 investigated the results of Am migration studies and concluded that the main forms of rare-earth carbonate ions in a water environment with pH 7-9 are RECO 3 + and RE(CO 3 ) 2…”
Section: àmentioning
confidence: 99%
“…This typically involves sample volumes of ca. 1 ml at concentrations around 10 −6 M or larger . As an example, for the actinide 241 Am such a sample has a radioactivity of ∼31 kBq (taking into account a specific activity of 3.43 Ci/g).…”
Section: Introductionmentioning
confidence: 99%